How can microfinance institutions successfully navigate a competitive advantage and financial performance? Exploring the role of ambidextrous leadership and intellectual capital - Syahrul Effendi; Idris Gautama So; Nugroho Juli Setiadi; Gatot Soepriyanto (Frontiers in Sociology, 2024)
The main objective of this study was to investigate how ambidextrous leadership contributes to competitive advantage and financial performance in Indonesia's microfinance institutions (MFIs). A secondary aim was to analyze the moderating effect of intellectual capital on the relationship between ambidextrous leadership and competitive advantage and the mediating role of competitive advantage in the indirect link between ambidextrous leadership and financial performance. Data were collected from 88 firms in the MFI sector through purposive sampling. The Moderation-Mediation (MODMED) procedure was used to assess four proposed relationships. The results indicated that ambidextrous leadership is crucial for achieving competitive advantage, with intellectual capital as a moderator in this relationship. Furthermore, competitive advantage was found to significantly explain financial performance and serve as an intermediary in the connection between ambidextrous leadership and financial performance. This study addresses the existing literature gap by examining ambidextrous leadership's influence on competitive advantage. It also introduces a fresh perspective by suggesting that intellectual capital acts as a boundary condition in the link between ambidextrous leadership and competitive advantage. The findings offer pragmatic insights for organizations, particularly MFIs in Indonesia, to enhance their competitive advantage through effective leadership and strategic management of intellectual resources.